Arabic Sociolinguistics - Bassiouney, Reem (Edinburgh University Press, 2022)
Reflects on the latest trends in the study of Arabic sociolinguistics New to this edition:A new chapter on Arabic critical sociolinguistics: the critical analysis of the field of sociolinguistics itself and its scholarly practicesExplains new theories such as language as a social construct, the relation between language and identity, stance, indexicality and translanguaging, with examples from areas not covered in the first editionDiscusses the political changes in the Arab world since 2011 and their impact on languageConsiders the role of new media in modifying theories and providing different kind of data for sociolinguistsThe second edition of Arabic Sociolinguistics offers an extended commentary on the important findings of new critical approaches to language and society in Arab-speaking countries. Following a recent wave of political upheavals in the Middle East, the book engages with latest academic works that relate language to power and conflict in the Arab world. In addition to thoroughly updated accounts of diglossia, code-switching, gender, language policy and language variation in the region, Reem Bassiouney discusses the most important recent development in the field - critical sociolinguistics - in a new dedicated chapter that challenges the tendency of applying Western linguistic methods and terms to superdiverse communities. By covering the key developments of linguistic theories and contexts with up-to-date examples to help explain the phenomena under discussion, this is the most comprehensive book on Arabic sociolinguistics today.Please note that Arabic Sociolinguistics is co-published by Georgetown University Press in the USA. If you in this area and are looking to buy a copy, or request a review or inspection copy, please direct orders and queries directly to them."